A resolução de problemas como metodologia para o ensino da multiplicação - Silva, Carine Ferreira da (Universidade do Vale do Rio dos Sinos, 2015)
This article reports research that was presented with the objective of understanding the interactions that occur during activities that call upon the methodology of problem resolution. The proposed activities were done with students in their sixth year of public school and was utilized for qualitative and quantitative analysis, for the data collection involved oral, written, and pictorial records. It was verified that the problem resolution methodology provoked in the students interaction, discussion, and the development of their capacity to interpret, formulate, and assess hypotheses. The activities carried out in classrooms prompted the students to reflect on their actions and develop their capacity to argue, resolving their problems with meaning.
Keywords: Resolução de problemas; Metodologia; Ensino da matemática; Significado; Problem resolution; Methodology; Mathematics teaching; Meaning